Screening of young children between 2-24 months of Age with a first febrile UTI for VUR with imaging modalities - Alkarani T Patil; Sanjeeva G N; Yogesh R; Sowmya K; Ramesh L (Pediatric Review: International Journal of Pediatric Research, 2015)
Background: Urinary tract infection (UTI) is one of the most common serious bacterial illnesses affecting children. The presence of moderate to severe vesicouretheral reflux (VUR), particularly if bilateral, is an important risk factor for pyelonephritis and renal scarring. Imaging studies, including renal ultrasonography (USG), technetium-99m– labelled dimercaptosuccinic acid (DMSA) scanning, and voiding cystourethrography (VCUG), are part of standard care after diagnosis of a first UTI in young children. This study was done to determine the sensitivity, specificity and predictive values of renal USG and DMSA scan findings for VUR.Methods: All children between 2-24 months of age presenting with first febrile UTI were prospectively studied. All infants were hospitalized and investigated using renal USG, DMSA scan, and VCUG after diagnosis. The association among findings of USG, DMSA scan, and VCUG were evaluated.Results: A total of 48 children were included in the study and screened, out of which there were abnormal results in 22 (45.8%) USG and 29(60.4%) DMSA scan. All grade VUR (I-V) was present in 8(16.7%) patients and high grade VUR (III-V) was present in 7(14.6%) patients. The sensitivities for detecting VUR of renal USG alone (75%) or DMSA scan alone (87.5%) were not as good as that of the “OR rule” strategy, which had 100% sensitivity and 100% negative predictive value.Conclusions: Renal USG and DMSA scanning both should be routinely performed in young children with a first febrile UTI. VCUG is only indicated when abnormalities are apparent on either USG scanning or DMSA scanning or both.